Retrospective study on the incidence and outcome of proven and probable invasive fungal infections in high-risk pediatric onco-hematological patients. - Cesaro, Simone; Tridello, Gloria; Castagnola, Elio; Calore, Elisabetta; Carraro, Francesca; Mariotti, Ilaria; Colombini, Antonella; Perruccio, Katia; Decembrino, Nunzia; Russo, Giovanna; Maximova, Natalia; Baretta, Valentina; et al. (Eur J Haematol, 2017)
BACKGROUND: Invasive fungal infection (IFI) is a cause of morbidity, mortality and increased health costs in children undergoing chemotherapy or hematopoietic stem cell transplant (HSCT). METHODS: Multicenter, retrospective study to assess the incidence, outcome of proven and probable IFI (PP-IFI) in children treated for acute leukemia, non-Hodgkin lymphoma or who underwent HSCT from 2006 to 2012. RESULTS: Over the 7-year period, 127 PP-IFI were diagnosed in 123 patients, median age of 9.7 years. The 1-year cumulative incidence was 2.5% (CI 1.8-3.7) after frontline chemotherapy, 9.4% (CI 5.8-15.0) after relapse, and 5.3% (CI 3.9-7.1) after HSCT. Severe neutropenia was present in 98 (77%) patients. Culture-proven agents were Candida spp., mostly non-albicans, 28, mold 23, whereas three proven IFI were identified by histopathology. Favorable response to treatment within 3 months from diagnosis was observed in 77 (89%). The overall ninety-day probability of survival was 68% (CI 59-76). CONCLUSIONS: About two-thirds of pediatric patients with PP-IFI survived, regardless of whether the infection occurred after frontline chemotherapy, reinduction chemotherapy for disease relapse, or after HSCT. Further prospective studies are needed to define the impact of antifungal prophylaxis and early combination therapy on short-term overall survival.
Keywords: Adolescent; Antifungal Agents; Antineoplastic Combined Chemotherapy Protocols; Child; Child, Preschool; Drug Therapy, Combination; Female; Hematologic Neoplasms; Hematopoietic Stem Cell Transplantation; Humans; Incidence; Male; Mycoses; Patient Outcome Assessment; Retrospective Studies; Survival Analysis; Treatment Outcome

Recommendations for the use of long-term central venous catheter (CVC) in children with hemato-oncological disorders: management of CVC-related occlusion and CVC-related thrombosis. On behalf of the coagulation defects working group and the supportive the - Giordano, Paola; Saracco, Paola; Grassi, Massimo; Luciani, Matteo; Banov, Laura; Carraro, Francesca; Crocoli, Alessandro; Cesaro, Simone; Zanazzo, Giulio Andrea; Molinari, Angelo Claudio (Ann Hematol, 2015)
Central venous catheters (CVC), used for the management of children with hemato-oncological disorders, are burdened by a significant incidence of mechanical, infective, or thrombotic complications. These complications favor an increasing risk in prolongation of hospitalization, extra costs of care, and sometimes severe life-threatening events. No guidelines for the management of CVC-related occlusion and CVC-related thrombosis are available for children. To this aim, members of the coagulation defects working group and the supportive therapy working group of the Italian Association of Pediatric Hematology and Oncology (AIEOP) reviewed the pediatric and adult literature to propose the first recommendations for the management of CVC-related occlusion and CVC-related thrombosis in children with hemato-oncological disorders.
Keywords: Adult; Blood Coagulation Disorders; Catheter Obstruction; Catheterization, Central Venous; Central Venous Catheters; Child; Hematologic Neoplasms; Humans; Risk Factors; Thrombosis

Single-day trimethoprim/sulfamethoxazole prophylaxis for Pneumocystis pneumonia in children with cancer. - Caselli, Désirée; Petris, Maria Grazia; Rondelli, Roberto; Carraro, Francesca; Colombini, Antonella; Muggeo, Paola; Ziino, Ottavio; Melchionda, Fraia; Russo, Giovanna; Pierani, Paolo; Soncini, Elena; DeSantis, Raffaella; et al. (J Pediatr, 2014)
OBJECTIVE: To determine whether a simplified, 1-day/week regimen of trimethoprim/sulfamethoxazole is sufficient to prevent Pneumocystis (jirovecii [carinii]) pneumonia (PCP). Current recommended regimens for prophylaxis against PCP range from daily administration to 3 consecutive days per week dosing. STUDY DESIGN: A prospective survey of the regimens adopted for the PCP prophylaxis in all patients treated for childhood cancer at pediatric hematology-oncology centers of the Associazione Italiana Ematologia Oncologia Pediatrica. RESULTS: The 20 centers participating in the study reported a total of 2466 patients, including 1093 with solid tumor and 1373 with leukemia/lymphoma (or primary immunodeficiency; n = 2). Of these patients, 1371 (55.6%) received the 3-day/week prophylaxis regimen, 406 (16.5%) received the 2-day/week regimen, and 689 (27.9%), including 439 with leukemia/lymphoma, received the 1-day/week regimen. Overall, only 2 cases of PCP (0.08%) were reported, both in the 2-day/week group. By intention to treat, the cumulative incidence of PCP at 3 years was 0.09% overall (95% CI, 0.00-0.40%) and 0.51% for the 2-day/week group (95% CI, 0.10%-2.00%). Remarkably, both patients who failed had withdrawn from prophylaxis. CONCLUSION: A single-day course of prophylaxis with trimethoprim/sulfamethoxazole may be sufficient to prevent PCP in children with cancer undergoing intensive chemotherapy regimens. This simplified strategy might have implications for the emerging need for PCP prophylaxis in other patients subjected to the increased use of biological and nonbiological agents that induce higher levels of immune suppression, such as those with rheumatic diseases.
Keywords: Anti-Infective Agents; Child; Dose-Response Relationship, Drug; Drug Administration Schedule; Follow-Up Studies; Hematologic Neoplasms; Humans; Incidence; Italy; Pneumocystis carinii; Pneumonia, Pneumocystis; Prospective Studies; Treatment Outcome; Trimethoprim, Sulfamethoxazole Drug Combination

Morbidity of pandemic H1N1 influenza in children with cancer. - Caselli, Désirée; Carraro, Francesca; Castagnola, Elio; Ziino, Ottavio; Frenos, Stefano; Milano, Giuseppe Maria; Livadiotti, Susanna; Cesaro, Simone; Marra, Nicoletta; Zanazzo, Giulio; Meazza, Cristina; Cellini, Monica; et al. (Pediatr Blood Cancer, 2010)
BACKGROUND: To define the mortality and the current impact of the H1N1 pandemic in pediatric hematology-oncology centers, we performed a specific survey. PROCEDURE: Pharyngeal swabs from patients with fevers of unknown origin, flu-like symptoms or bronchopneumonia were screened for H1N1 using PCR. RESULTS: Sixty-two patients with documented H1N1 infection were reported: 16 had recently stopped therapy, 2 were at the diagnosis stage, and 44 were receiving therapy. The clinical course was severe (requiring ICU admission) in only 1 patient, moderate (requiring hospital admission) in 38, and mild in the remaining 23 (37%), treated as outpatients. While none of the patients died of H1N1-related complications, two patients died of progressive cancer; in all of the remaining cases, symptoms resolved within 11 days. The clinical course was complicated by respiratory distress or bronchopneumonia in 10 cases. Oseltamivir was given to 82% of patients. Chemotherapy was temporarily withdrawn in 54% of cases for a median time of 21 days (range, 4-43 days). CONCLUSION: H1N1 infection in children with cancer was not reported as the cause of death in any case but resulted in reduced intensity of anti-cancer therapy.
Keywords: Adolescent; Antineoplastic Agents; Cause of Death; Child; Child, Preschool; Data Collection; Disease Outbreaks; Humans; Influenza A Virus, H1N1 Subtype; Influenza, Human; Leukemia; Lymphoma, Non-Hodgkin; Morbidity; Neoplasms; Treatment Outcome; Young Adult